Analisis User Interface Pada Website E-Learning2 Bina Darma Menggunakan Metode Evaluasi Heuristik - Raihan, Mohammad; Panjaitan, Febriyanti; Jemakmun, H.; Sauda, Siti (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The development of information and communication technology has changed many aspects of life, including in the field of education. One of its implementations is the use of e-learning systems as a means of distance learning. E-learning offers flexibility and ease of access for students, so that more and more educational institutions are implementing it. Bina Darma University, as one of the higher education institutions in Indonesia, has also developed an e-learning system known as E-learning2 Bina Darma. This system is an important tool for lecturers and students in carrying out the online teaching and learning process. The success of e-learning implementation is not only determined by the availability of adequate features and content, but also depends on the design and usability of a good user interface. An easy-to-use and intuitive user interface will improve the user experience and motivate students to actively participate in e-learning. Therefore, it is very important to assess and improve the user interface to ensure that the e-learning system can be used optimally. One effective method for assessing the usability of a user interface is heuristic evaluation. This method involves examining the user interface based on a set of established heuristic principles, as proposed by Jakob Nielsen. Heuristic evaluation can identify problems and weaknesses in the user interface, and provide recommendations for improvements that can improve the user experience and overall usability of the system. This study aims to analyze the user interface of the E-learning2 Bina Darma website using the heuristic evaluation method. The results of this study are expected to provide useful input for Bina Darma University in improving the quality and usability of the e-learning2 system, so that it can support a more effective and interesting learning process for students.